Impact of thrombocytopenia-associated c.-118C>T and c.-140C>G ANKRD26 5’UTR variants in three-generational pedigree - Jakub Trizuljak; Paulína Likavcová; Kateřina Staňo Kozubík; Zuzana Vrzalová; Jakub Hynšt; Tereza Deissová; Jiří Štika; Lenka Radová; Marie Prudková; Jana Vaculová; Ivona Blaháková; Petr Smejkal; et al. (Platelets)
Inherited thrombocytopenias (ITs) encompass a group of rare disorders characterized by diminished platelet count. Recent advancements have unveiled various forms of IT, with inherited thrombocytopenia 2 (THC2) emerging as a prevalent subtype associated with germline variants in the critical 5’ untranslated region of the ANKRD26 gene. This region is crucial in regulating the gene expression of ANKRD26, particularly in megakaryocytes. THC2 is an autosomal dominant disorder presenting as mild-to-moderate thrombocytopenia with minimal symptoms, with an increased risk of myeloproliferative malignancies. In our study of a family with suspected IT, three affected individuals harbored the c.-118C>T ANKRD26 variant, while four healthy members carried the c.-140C>G ANKRD26 variant. We performed a functional analysis by studying platelet-specific ANKRD26 gene expression levels using quantitative real-time polymerase-chain reaction. Functional analysis of the c.-118C>T variant showed a significant increase in ANKRD26 expression in affected individuals, supporting its pathogenicity. On the contrary, carriers of the c.-140C>G variant exhibited normal platelet counts and no significant elevation in the ANKRD26 expression, indicating the likely benign nature of this variant. Our findings provide evidence confirming the pathogenicity of the c.-118C>T ANKRD26 variant in THC2 and suggest the likely benign nature of the c.-140C>G variant.